Articles made from heavy plastic materials

By adding an appropriate amount of metal and/or ceramic filler to the heavy-duty plastic material, and combining an appropriate amount of polymer and optional adhesive, a composite material is formed by chemical bonding such as hydrogen bonds, which solves the problem of degradation of mechanical properties of existing materials and achieves high-impact resistance and good mechanical properties.

JP7667201B2Active Publication Date: 2025-04-22ETA SA MFG HORLOGERE SUISSE
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023077047
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-05-11
Filing Date
2023-05-09
Publication Date
2025-04-22
Estimated Expiration
2043-05-09

AI Technical Summary

Technical Problem

After adding metal or ceramic fillers, existing heavy-duty plastic materials have reduced mechanical properties, especially their performance in terms of impact resistance and ductility, and are difficult to meet applications that require high-impact resistance.

Method used

A new composite material is formed by introducing 50% to 85% metal and/or ceramic filler into the material and combining 15% to 50% polymer with optional 0% to 10% binder, 0% to 10% reinforcement, 0% to 5% pigment and 0% to 5% stretching or plasticizer. This material improves the bonding force between the filler and the polymer through the formation of chemical bonds such as hydrogen bonds, ion bonds and coordination bonds.

Benefits of technology

The high density, good rigidity, sufficient ductility and high tensile strength of the material are achieved, which meets the mechanical performance requirements in time measurement applications, while maintaining the lightness of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007667201000008
    Figure 0007667201000008
  • Figure 0007667201000009
    Figure 0007667201000009
  • Figure 0007667201000010
    Figure 0007667201000010
Patent Text Reader

Abstract

To provide an item made of a heavy plastic material that enhances the cohesion of the material and thereby enhances the mechanical properties of the material.SOLUTION: An item is made from a material comprising, by weight, a metallic and / or ceramic filler present at greater than or equal to 50% and less than or equal to 85%, at least one polymer present at greater than or equal to 15% and less than or equal to 50%, and optionally at least one binder present at greater than or equal to 0% and less than 10%. When the polymer is bound to the filler and / or the material comprises at least one binder, the binder is bound to each of the polymer and the filler by one or more hydrogen bonds. The polymer and / or the binder comprises a hydrogen bond donor. The hydrogen bond donor is a NHX group adjacent to a hydrogen bond acceptor which is a C=O group so as to form a -[(C=O)NH] - unit, the - [(C=O) NH] - unit corresponding to at least 1 mol% of the polymer and / or of the binder.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to articles, such as timepiece components, made from heavy impact resistant plastic materials.

[0002] The present invention also relates to a method for manufacturing such an article made from heavy plastic. [Background technology]

[0003] Many of the external components, such as the middle part and the band, are made of plastic materials. These components can be produced using a molding method, which offers the advantage of being available in a variety of shapes without any modification. These plastic material components are characterized by having a density close to 1 and therefore being lightweight. This can be a drawback for users who want to wear a watch with a certain weight on their wrist.

[0004] To remedy this drawback, it has been proposed, for example in document EP 2 482 142, to produce timepiece components, whether movement or external components, in plastic material filled with a high density metal powder, such as tungsten powder, these components being produced using an injection moulding method, which makes it possible to retain the advantages of moulding in a mould without subsequent modification, whilst increasing the density of the components.

[0005] These materials thus combine the advantages of plastics, such as the ease of molding by injection, with the advantages of metals, such as density, cool feel and metallic appearance.

[0006] However, a reduction in resistance to breakage and elongation can be observed in these materials compared to the host polymer matrix. This reduction is due to the lack of material cohesion due to the incorporation of micrometer-sized metal powders into nanometer-sized polymer chains. This loss of properties due to the lack of material cohesion is therefore observed in materials containing metal (or ceramic) fillers, polyolefins (polyethylene, polypropylene) as polymers, and polyurethane as binder.

[0007] This reduction in mechanical properties affects the shock absorbing capacity of the material, and therefore this type of material is not suitable for applications requiring shock resistance, for example in the field of timekeeping instruments to produce intermediate parts etc. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] European Patent No. 2482142 Summary of the Invention [Problem to be solved by the invention]

[0009] It is an object of the present invention to provide a novel heavy plastic material composition which improves the bonding strength of the material and thereby improves the mechanical properties of the material.

[0010] The invention finds particularly interesting applications in the field of watchmaking, although the invention is not limited to such applications. [Means for solving the problem]

[0011] To this end, the present invention provides an article, which comprises, by total weight of 100%, -3g / cm 3 a filler made of a metal and / or ceramic material having a density equal to or greater than 50%, said filler being present in a percentage equal to or greater than 50% and equal to or less than 85%; - at least one polymer present in a percentage of 15% or more and 50% or less; - optionally at least one binder present in a percentage greater than or equal to 0% and less than 10%; - optionally at least one reinforcing agent present in a percentage between 0 and 10%; - optionally at least one pigment present in a percentage between 0 and 5%; - optionally at least one spreading agent and / or plasticizer present in a percentage between 0 and 5%; The present invention is made from a material comprising:

[0012] According to the invention, the polymer is bonded to the filler and / or the binder, if the material comprises at least one binder, is bonded to the filler and the polymer, respectively, by one or more hydrogen bonds.

[0013] The polymer and / or binder comprises a hydrogen bond donor, which is an NH bond adjacent to a hydrogen bond acceptor that is a C=O group to produce a -[(C=O)NH]- unit. X It is based on

[0014] The -[(C=O)NH]- units represent at least 1 mol % of the polymer and / or binder.

[0015] These hydrogen bonds that bind the filler, the polymer and, if applicable, the binder, make it possible to ensure good cohesion of the materials. These hydrogen bonds have an interaction energy that is typically less than 100 kJ / mol or even 50 kJ / mol, and are characterized in that they allow the bonds between the molecules to be broken during the increase in temperature during the manufacturing process, thus ensuring better mixing of the materials and better cohesion after cooling and bond reformation.

[0016] The material according to the invention has sufficient stiffness with a Young's modulus of 2.5 GPa or more, sufficient elongation at break of 5% or more, and sufficient tensile strength of 30 MPa or more for timekeeping applications. The material according to the invention has good toughness and a modulus of 2 to 7 g / cm 3 It also has a density between .

[0017] In addition to these characteristics mentioned in the previous paragraphs, the article according to the invention may have one or more complementary characteristics, taken on an individual basis or in any technically possible combination, from among the following: the filler is present in a weight percentage between 60 and 80% and the polymer is present in a weight percentage between 20 and 40%, the filler is present in a weight percentage between 65 and 75% and the polymer is present in a weight percentage between 25 and 35%, the filler is present in a weight percentage between 50 and 75% and the polymer is present in a weight percentage between 25 and 50%, the filler is present in a weight percentage between 50 and 65% and the polymer is present in a weight percentage between 35 and 50%, the binder is present in a weight percentage between 0.1 and 10%, the binder is present in a weight percentage between 0.1 and 5%, the binder is present in a weight percentage between 0.5 and 3%, - the metal and / or ceramic material comprises a coordination and ionic bond with a polymer and / or binder on the electron hole contained in the surface oxide, hydroxide and / or hydrogen; -The polymer and / or binder is NH X , having one or more groups selected from OH, COC, C═O and COOH; the polymer is a polyamide, preferably polyamide 11; the binder is a polyurethane; - the polymer is bound to the filler and / or, if the material comprises at least one binder, the binder is bound to the polymer and to the filler by one or more ionic bonds, respectively, and the polymer is bound to anions of the filler and / or the binder, NH X + group, the filler has an O- anion, the binder has an R-COO- anion, the polymer is bonded to the filler and / or, if the material comprises at least one binder, the binder is bonded to the polymer and to the filler, respectively, by one or more coordinate bonds, the polymer and / or the binder having amine or carboxylic acid functional groups which form said coordinate bonds with electron holes on the surface of the filler, the binder contains at least 20 carbon atoms, the material comprises a filler and a polymer which is polyurethane, without the addition of said binder; the material comprises a filler, a polyamide as polymer and a polyurethane as binder; the material comprises, in percentages of 100%, a percentage between 65 and 80% of said filler, a percentage between 19.5 and 34.5% of said polymer and a percentage between 0.5 and 5% of said binder, the material comprises, in percentages of 100%, a percentage between 65 and 75% of said filler, a percentage between 24 and 34% of said polymer and a percentage between 1 and 3.5% of said binder, the material comprises, in percentages of 100%, a percentage between 50 and 75% of said filler, a percentage between 24.5 and 49.5% of said polymer and a percentage between 0.5 and 5% of said binder, the material comprises, in percentages of 100%, a percentage between 50 and 65% of said filler, a percentage between 34.5 and 49.5% of said polymer and a percentage between 0.5 and 5% of said binder, the material comprises a filler with a polyamide as polymer and a hydroxysilane with amide or amine functionality as a binder; the material comprises a filler with a polyester as polymer and a hydroxysilane with amide or amine functionality as a binder; the reinforcing agent is present in a weight percentage between 1 and 6%, the reinforcing agent is formed from glass fibres, glass beads, carbon fibres and / or aramid fibres; The article is an external part of a timepiece or a movement component.

[0018] Furthermore, the invention relates to methods for producing this material by molding, injection or 3D printing.

[0019] The method comprises providing a filler matrix of at least 0.01 m to provide a filler having sufficient reactive surface area to form hydrogen bonds and any complementary ionic and / or coordinate bonds with the polymer and / or binder, if present. 2 / g, preferably 2m 2 / g, more preferably 5m 2 / g or more. The reactive surface area therefore includes hydroxides, oxides and / or electron holes, regardless of the type of ceramic (oxide, nitride or carbide) or metal (steel, tungsten, etc.).

[0020] Further features and advantages of the invention will become apparent from the following description of preferred embodiments given as non-limiting examples with reference to the attached drawings, in which: [Brief description of the drawings]

[0021] [Figure 1] FIG. 1 is a diagram of a timepiece with an intermediate part made from a heavy plastic material according to the invention. [Diagram 2] FIG. 2 is a schematic diagram showing the interactions between the surface of a filler, a binder, and a polymer. [Diagram 3]FIG. 2 is a schematic diagram showing hydrogen bonds formed between a filler, a binder, and a polymer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] The present invention relates to articles made from composite materials comprising a plastic material and a metal or ceramic material.

[0023] For example, the article may be a component of a watch, a piece of jewelry, a band, etc.

[0024] The article may also be a component of a bezel, for example a base, an arm, or a base.

[0025] In a non-limiting and non-exhaustive manner, an article according to the present invention may be, or may entirely form, an article of sporting goods, an article of cookware, a musical article or instrument, an article of leather or sewing goods, a component of an automobile or aircraft, a component of an electronic article (e.g., a protective phone case, a computer keyboard, computer keyboard keys, a headset, etc.), a writing instrument, etc.

[0026] Advantageously, the article is a component or part of a component, the function of which requires a particular resistance to impacts and shocks.

[0027] In the particular field of watchmaking, this article may be, for example, an external component such as an intermediate part, a back, a bezel, a button, a band ring, a dial, a hand, a scale on the dial, etc.

[0028] By way of example, an intermediate part 1 made from the material of the invention is shown in FIG.

[0029] According to another embodiment example (not shown), the article according to the invention may be a component of a movement, such as for example a plate.

[0030] According to the invention, the article is made from a material that includes two main components: a metal and / or ceramic filler and a polymer, and the material is therefore referred to as a composite material.

[0031] Optionally, the material may comprise one or more binders if the physicochemical interaction between the filler and the polymer is not sufficient according to the type of application and if an even further increase in the impact resistance of the already reinforced material according to the invention is required.

[0032] Optionally, the material may also include a reinforcing agent.

[0033] Optionally, the material may also include one or more pigments.

[0034] Optionally, the material may also include a spreading agent and / or a plasticizer.

[0035] The filling material may be metallic and / or ceramic.

[0036] The metallic material may comprise conventional carbon steel, stainless steel, copper, copper alloys, titanium, titanium alloys, or tungsten. Preferably, the metallic material comprises nickel-free stainless steel.

[0037] The ceramic material may consist of carbides, nitrides or oxides such as ZrO2, CeO2, ZnO, etc.

[0038] The filler may also comprise a filler including a mixture of metallic and ceramic materials.

[0039] The filler is present in a weight percentage of not less than 50% and not more than 85% by weight of the material.

[0040] For example, the filler may be between 50 and 75% by weight (inclusive) of the material.

[0041] For example, the filler may be between 50 and 65% by weight (inclusive) of the material if a relatively low density material is desired.

[0042] For example, the filler may be between 60 and 80% by weight (inclusive) of the material, such as between 65 and 75% by weight if a further increase in material density is desired.

[0043] Advantageously, in the above examples, the filler as a whole is the majority by weight, ie greater than 50% by weight of the material.

[0044] According to the invention, the filler is provided with a high specific surface area (≧0.01 m) during the manufacturing process. 2 The filler is introduced in the form of a powder having a composition of 0.1 to 0.5 wt. / g, which, in the absence of any specific treatment, has compositional modifications and / or defects on its surface, regardless of the type of metal or ceramic filler. The filler can consist of defects such as oxides or hydroxides and electron holes present on the oxidized surface of the powder, which allow various hydrogen bond mediated interactions with the polymer and / or binder, if present. Thus, FIG. 2 shows diagrammatically the interactions established between the surface of the filler 2 and the binder 3 and polymer 4, if the material includes a binder.

[0045] The material comprises one or more polymers capable of hydrogen bond formation, in addition to ionic and / or coordinate bonds with the filler and / or optionally with the binder, if present. All such physicochemical bonds, and especially hydrogen bonds, are characterized by having a low interaction energy, typically between 5 and 100 kJ / mol, allowing the bonds between the molecules to be broken during the temperature increase during the injection or 3D printing of the material. These physicochemical bonds are regenerated during the cooling of the material after injection or 3D printing. This feature allows for better mixing, better compatibility between the components, and therefore better cohesion of the material on a molecular scale, and therefore a better overall cohesion of the material.

[0046] The polymer or set of polymers represents a weight percentage of between 15 and 50% of the material (inclusive).

[0047] For example, the polymer or set of polymers may represent a weight percentage of between 25 and 50% of the material (inclusive).

[0048] For example, the polymer or set of polymers may represent a weight percentage of between 35 and 50% of the material (inclusive).

[0049] For example, the polymer or set of polymers may represent a weight percentage of between 20 and 40%, such as between 25 and 35%, of the material (inclusive).

[0050] If the filler is the majority of the material, the polymer or set of polymers will be a percentage less than 50% by weight.

[0051] Advantageously, the polymer or set of polymers is selected to form hydrogen bonds with the filler. For this purpose, the polymer or set of polymers comprises hydrogen bond donors comprising groups with hydrogen atoms, such as NH or OH groups, and hydrogen bond acceptors comprising groups with atoms more electronegative than hydrogen, such as atoms of nitrogen, oxygen or halogen groups, such as fluorine, chlorine, bromine, etc. Hydrogen bonds are formed with hydroxides and oxides present on the oxidized surface of the metal or ceramic filler.

[0052] For example, the hydroxide groups on the surface of the filler can be easily substituted with C=O, R-OH, COC, and R-NH of the polymer. X Interacts with the R' group.

[0053] Preferably, the hydrogen bond donor and acceptor are adjacent on the polymer chain.

[0054] Preferably, the polymer or set of polymers comprises a hydrogen bond donor, the hydrogen bond donor being an NH group adjacent to a hydrogen bond acceptor that is a C=O group to generate a -[(C=O)NH]- unit. X It is based on

[0055] Preferably, the polymer or set of polymers may be a polyamide of RC(=O)-NH-R' chains, thus comprising -[(C=O)NH]- units, such that the C=O group containing the bond acceptor oxygen atom and the NH group containing the bond donor hydrogen atom are adjacent.

[0056] Preferably, the -[(C=O)NH]- units represent at least 1% of the polymer or set chains of the polymer.

[0057] Preferably, the polymer is a polyamide, such as polyamide 11, that is bio-based and renewable in source.

[0058] Additionally, ionic and / or coordinative bonds may be formed between the polymer and the filler, creating additional interactions and further strengthening the cohesive strength of the materials.

[0059] Ionic bonds within the scope of the present invention result from the interaction between negatively charged basic functional groups and positively charged acidic functional groups. Ionic bonds result from the interaction between negatively charged basic functional groups and positively charged acidic functional groups. + It is produced by transferring ions to a polymer. For example, the polymer is NH X More specifically, after the acid-base reaction, R-NH X+1 -R'+ / MO- can be the resulting polyamide.

[0060] A coordinate bond is a special covalent bond in which the shared electron doublet is only obtained from one of the atoms, as opposed to a conventional covalent bond in which one electron is obtained from each of the bond electrons. According to the present invention, this coordinate bond requires, more specifically, a Lewis base generated by the polymer, which is associated with an electron hole on the surface of the filler that generates a Lewis acid. Any polymer with a functional group that contains an atom with a non-bonded pair can share this pair to "stabilize" the electron hole. For example, the polymer can be composed of a non-bonded pair of nitrogen or oxygen in R(C=O)NR', ​​RO(C=O)NR' and R(C=O)OR'. The polymer can be composed of an amine (NH X) or carboxylic acid (COOH) functional groups, and amine (NH X ) or carboxylic acid (COOH) functional groups can form this coordinate bond with the electron holes on the surface of the filler. Examples include polyurethanes and polyesters.

[0061] The material may contain a binder in a percentage between 0% and less than 10%, advantageously between 0.1 and 10%, more advantageously between 0.1 and 5%, even more advantageously between 0.5 and 3%.

[0062] The use of a binder makes it possible to further enhance the mechanical properties, in particular the impact resistance, of articles made from such materials according to the invention.

[0063] The binder can be bonded to the filler and the polymer primarily by one or more hydrogen bonds, which may replace or supplement the hydrogen bonds between the polymer and the filler, depending on the nature of the polymer used.

[0064] The ionic and / or coordinative bonds described above may also generate additional interactions that further strengthen the bonding strength of the materials, i.e., between the binder and the filler and between the binder and the polymer.

[0065] It is noted that in the presence of a binder, hydrogen bonds are formed primarily between the binder and the filler and between the binder and the polymer, without necessarily direct hydrogen bonds between the filler and the polymer. For polymers, the binder may be C=O, COC, OH, NH X or COOH.

[0066] Preferably, the hydrogen bond donor and acceptor are adjacent on the binder chain.

[0067] Preferably, the linking agent comprises a hydrogen bond donor, the hydrogen bond donor being an NH bond adjacent to a hydrogen bond acceptor that is a C=O group to generate a -[(C=O)NH]- unit. X It is based on

[0068] Preferably, the -[(C=O)NH]- units represent at least 1% of the chains of the binder.

[0069] Preferably, the binder is a polyurethane containing -[OC=O-NH]- units.

[0070] Preferably, the binder has a chain length of at least 20 carbon atoms.

[0071] Also by way of example, the linking agent may be a hydroxysilane having an amide or amine functionality on the chain, and preferably at least 20 carbon atoms, allowing for hydrogen, ionic and / or coordinate bonding.

[0072] For example, the binder also reacts with ions H from OH groups on the surface of the filler. + This transfer allows for the creation of ionic bonds due to acid-base reactions that occur between the filler and the binder during the manufacturing process.

[0073] The binder may also form an ionic bond between the binder and the polymer. The polymer may be a carboxylic acid COOH that forms a base and an amine R'-NH X Each of them contains one or the other of the functional groups, and after the acid-base reaction, RCOO- / R'-NH X You get +1+.

[0074] Alternatively, the polymer and binder may already be charged before contact. In this case, in the above example, the binder and polymer may each have a basic functional group RCOO- or an acidic functional group R'-NH X+1 +.

[0075] Optionally, the material may also contain a reinforcing agent in a weight percentage between 0 and 10%, preferably between 0% (excl. 0%) and less than or equal to 10%, advantageously between 1 and 6% (inclusive). The reinforcing agent may be present in various forms, for example in the form of fibers or particles. For example, the reinforcing agent may consist of glass fibers, glass beads, carbon fibers and / or aramid fibers, with a fiber length of less than or equal to 300 μm, and preferably less than or equal to 200 μm. The purpose of the reinforcing agent is to enhance the toughness of the material, to limit the shrinkage of the material during injection and / or to enhance the electrical conductivity of the material.

[0076] Optionally, the material may also include one or more pigments, with a total percentage between 0 and 5% by weight, preferably between 0% (exclusive) and 5% or less. The pigments may be organic or inorganic. For example, the pigments may consist of carbon black for black, diketopyrrolopyrrole for red (e.g., Irgazin Red K3840LW by BASF), copper phthalocyanine for blue (e.g., Heliogen Blue K7096 by BASF), monoazo pigment for yellow (e.g., Paliotol Yellow K1760 by BASF), etc.

[0077] Optionally, the material may also contain spreading agents and / or plasticizers such as waxes (paraffin) or other useful resins (terpene, phenolic, etc.) to facilitate packaging during manufacturing. All of these spreading agents and plasticizers are present in an amount between 0 and 5% by weight, preferably between 0% (exclusive) and 5% or less.

[0078] For example, as represented by Figure 3, the material comprises a metal filler M and / or a ceramic filler 2, a polyamide as polymer 4 and a polyurethane as binder 3, preferably having at least 20 carbon atoms.

[0079] Polyamide P11 is derived from castor oil and is therefore a renewable source, therefore the material provided by the present invention is a bio-based material.

[0080] In this example, the hydrogen bonds between the polymer, binder and filler are represented by dotted lines.

[0081] For example, a material may have a weight percentage of: a percentage of between 65 and 80% by weight, for example between 65 and 75%, or between 50 and 75% by weight, for example between 50 and 65%, of metal fillers, such as stainless steel, and / or ceramic fillers, such as zirconium oxide; a percentage by weight of polyamide between 19.5 and 34.5%, for example between 24 and 34%, or between 24.5 and 49.5%, for example between 34.5 and 49.5%, - a percentage of polyurethane between 0.5 and 5%, for example between 1 and 3.5% Includes.

[0082] For example, a material may have a weight percentage of: a ceramic filler, such as zirconium oxide, in a percentage by weight between 65 and 80%, for example between 65 and 75%, or between 50 and 75%, for example between 50 and 65%, a percentage by weight of a polyamide, such as polyamide 11, between 19.5 and 34.5%, for example between 24 and 34%, or between 24.5 and 49.5%, for example between 34.5 and 49.5%, - a percentage of polyurethane between 0.5 and 5%, for example between 1 and 3.5% Includes.

[0083] Such materials, which combine ceramic materials with renewable sourced biological materials, are called bioceramic materials.

[0084] For example, the material may include metal and / or ceramic fillers and polyurethane, which acts as both the polymer and the binder, and thus in this example, no binder separate from the polymer is needed, since the interaction between the fillers and the polymer is sufficient to ensure good cohesion of the material after this step.

[0085] For example, the material comprises metal and / or ceramic fillers, a polyamide as the polymer, and a hydroxysilane with amide or amine functionality as the binder, the binder advantageously comprising at least 20 carbon atoms.

[0086] For example, the material may include metal and / or ceramic fillers, a polyester as the polymer, and a hydroxysilane with amide or amine functionality as the binder, the binder preferably containing at least 20 carbon atoms.

[0087] The article is manufactured by molding, injection or 3D printing. The method is characterized in that the BET of the filler powder must be sufficient to obtain a reactive surface area. More specifically, the filler matrix has a surface area of ​​less than 0.01 m2 measured according to the 2010 ISO 9277 standard. 2 / g or more, preferably 2m 2 / g, more preferably 5m 2 / g BET specific surface area.

[0088] In the case of injection molding, the manufacturing process comprises the following steps, referring to the fillers, polymers, binders, reinforcing agents and pigments described above: a) preparing granules of a few millimeters, the granules comprising, by weight: -3g / cm 3 metal and / or ceramic fillers having a density equal to or greater than 50% and present in a percentage of 50% or more and 85% or less, for example between 60 and 80%, for example between 65 and 75%, for example between 50 and 75%, for example between 50 and 65%; - polymer(s) present in a percentage overall of 15% or more and 50% or less, for example between 20 and 40%, for example between 25 and 35%, for example between 25 and 50%, for example between 35 and 50%, - optionally at least one binder present in a percentage greater than or equal to 0% and less than 10%, advantageously between 0.1 and 10%, more advantageously between 0.1 and 5% and even more advantageously between 0.5 and 3%, - optionally a reinforcing agent present in a percentage between 0 and 10%, - optionally, pigment(s) present in a percentage between 0 and 5%, Optionally, a spreading agent and / or plasticizer, or a mixture of spreading agents and / or plasticizers, said spreading agent and / or plasticizer, or said mixture of spreading agents and / or plasticizers, being present in a percentage between 0 and 5%. and b) injection molding the granules, for example by overmolding onto another part, to form an article or part of an article; The injection is carried out in a mold having a temperature between 60 and 100°C, preferably between 70 and 80°C, while the material being injected has a temperature between 200 and 300°C, preferably between 250 and 300°C.

[0089] In step a), the granules may be produced by punching the cylinders obtained from the extrusion of the above-mentioned raw materials. Advantageously, if a binder is present, it is introduced into the hopper of the extruder in a first stage, separately or together with the polymer granules, before the introduction of the metal or ceramic powder into the extruder in the second stage. When the binder is introduced separately, it may be introduced in the form of a powder having a d90 of less than or equal to 500 μm, preferably 315 μm, or in the form of a liquid. The pigment may be introduced during extrusion, advantageously in the second stage. It may also be envisaged to mix the polymer with the granules immediately before extrusion.

[0090] According to an alternative embodiment, the metal or ceramic material and, if present, a binder are introduced into the hopper of the extruder in a first stage, so as to coat the metal or ceramic powder with the binder before the polymer and reinforcing agent are introduced.

[0091] Alternatively, the article may be manufactured by 3D printing, such as FDM (fused deposition modeling).

[0092] The resulting article comprises a metal and / or ceramic material, a plastic material including a polymer, and optionally a binder, the product resulting from the reaction between the filler, the polymer, and the binder during extrusion or injection, and further comprises a reinforcing agent and a pigment, if present.

[0093] The article according to the present invention has a Young's modulus of 2.5 GPa or more, an elongation at break of 5% or more, and a tensile strength of 30 MPa or more, these properties being measured according to the 2019 ISO 527-1A standard.

[0094] For example, tests were carried out to produce intermediate parts by injection from cylindrical granules having a diameter of about 4 mm and a length of about 1.5 mm.

[0095] Tables 1 and 2 below take two example embodiments with the properties obtained before and after 24 hours of conditioning in a ventilated oven without humidity control at 60° C. Izod mechanical elasticity tests on intermediate parts further demonstrated good toughness of intermediate parts produced with the above-mentioned compositions.

[0096] Table 3 shows an example of a material composition according to the present invention without the use of a binder.

[0097] Table 4 shows the composition Comp1 of an article made from heavy plastic material according to the prior art, in particular according to document EP 3 674 816.

[0098] Table 5 shows a first variant Comp2 of the prior art composition Comp1, which does not use reinforcing fibres.

[0099] Table 6 shows a second variant Comp3 of the prior art composition Comp1, in which the proportions of filler, polymer and binder are the same as in the examples according to the invention Inv1, Inv2. Such a variant allows highlighting the advantages and improvements in the binding strength of the material obtained with respect to the material described in document EP 3 674 816.

[0100] Table 7 is a summary table compiling various stiffness, elongation at break and stress at break properties for compositions according to the invention (Inv1, Inv2, Inv3) and prior art compositions (Comp1, Comp2, Comp3).

[0101] Comparison of Examples 1 (Inv1), 2 (Inv2) and 3 (Inv3) with prior art Examples 4 (Comp1), 5 (Comp2) and 6 (Comp3) shows the benefit of the specific selection of polymers to enhance the bonding strength with the filler, particularly through the formation of hydrogen bonds with the filler.

[0102] The use of a good binder allows further enhancement of the article properties (Example 3 and Example 1).

[0103] TIFF0007667201000001.tif91170Table 1-Example 1-Inv1

[0104] TIFF0007667201000002.tif81170 Table 2 - Example 2 - Inv2

[0105] TIFF0007667201000003.tif71170 Table 3 - Example 3 - Inv3

[0106] TIFF0007667201000004.tif91170 Table 4 - Example 4 - Composition 1 (Comp1)

[0107] TIFF0007667201000005.tif71170 Table 5 - Example 5 - Composition 2 (Comp2) (Composition 1 without reinforcing fibers)

[0108] TIFF0007667201000006.tif71170 Table 6 - Example 6 - Composition 3 (Comp3)

[0109] TIFF0007667201000007.tif101170Table 7 - Comparison of Example 1, Example 2, Example 3, Example 4, Example 5 and Example 6 - () indicates characteristics before and after averaging [Explanation of symbols]

[0110] 2 Filling material 3. Binder 4. Polymers

Claims

1. It is made from materials with a density of 2 to 7 g / cm 3 and wherein the material is, by weight, 100% of the total weight, -3 g / cm 3 A filler (2) made of a metallic material and / or a ceramic material having a density equal to or greater than 50%, wherein the metallic material is made of carbon steel, stainless steel, copper, copper alloy, titanium, titanium alloy or tungsten, and the ceramic material is made of ZrO 2 , CeO 2 , ZnO, and the filler (2) is present in a weight percentage of 50% or more and 85% or less; - at least one polymer (4) present in a weight percentage equal to or greater than 15% and equal to or less than 50%; - optionally at least one binder (3) present in a weight percentage greater than or equal to 0% and less than 10%; - optionally at least one reinforcing agent present in a weight percentage between 0 and 10%, the reinforcing agent being formed from glass fibers, glass beads, carbon fibers and / or aramid fibers; - optionally at least one pigment present in a weight percentage between 0 and 5%; - optionally at least one spreading agent and / or plasticizer present in a weight percentage between 0 and 5%; wherein the polymer (4) is bonded to the filler (2) and / or, if the material comprises at least one binder (3), the binder (3) is bonded to each of the polymer (4) and the filler (2) by one or more hydrogen bonds; the polymer (4) and / or the binder (3) are characterized in that they contain a hydrogen bond donor, which is an amine functional group adjacent to a hydrogen bond acceptor, which is a C=O group, so as to generate a -[(C=O)NH]- unit; the -[(C=O)NH]- units represent at least 1 mol % of the polymer (4) and / or the binder (3); the polymer (4) is a polyamide or polyamide 11 and the binder (3) is a polyurethane; 2. An article, characterized in that the article is comprised of an external timepiece part or movement component.

2. It is made from materials with a density of 2 to 7 g / cm 3 and wherein the material is, by weight, 100% of the total weight, -3 g / cm 3 A filler (2) made of a metallic material and / or a ceramic material having a density equal to or greater than 50%, wherein the metallic material is made of carbon steel, stainless steel, copper, copper alloy, titanium, titanium alloy or tungsten, and the ceramic material is made of ZrO 2 , CeO 2 , ZnO, and the filler (2) is present in a weight percentage of 50% or more and 85% or less; - at least one polymer (4) present in a weight percentage equal to or greater than 15% and equal to or less than 50%; - optionally at least one reinforcing agent present in a weight percentage between 0 and 10%, the reinforcing agent being formed from glass fibers, glass beads, carbon fibers and / or aramid fibers; - optionally at least one pigment present in a weight percentage between 0 and 5%; - optionally at least one spreading agent and / or plasticizer present in a weight percentage between 0 and 5%; Including, The polymer (4) is characterized in that it comprises a hydrogen bond donor, which is an amine functional group adjacent to a hydrogen bond acceptor, which is a C=O group, so as to generate a -[(C=O)NH]- unit; The -[(C=O)NH]- unit represents at least 1 mol % of the polymer (4); The material comprises the filler (2) and the polymer (4) which is polyurethane; 2. An article, characterized in that the article is comprised of an external timepiece part or movement component.

3. 3. An article according to claim 1 or 2, characterized in that said filler (2) is present in a weight percentage between 50 and 80% and said polymer (4) is present in a weight percentage between 20 and 40%.

4. 3. An article according to claim 1 or 2, characterized in that said filler (2) is present in a weight percentage between 50 and 75% and said polymer (4) is present in a weight percentage between 25 and 35%.

5. 3. An article according to claim 1 or 2, characterized in that said filler (2) is present in a weight percentage between 50 and 75% and said polymer (4) is present in a weight percentage between 25 and 50%.

6. 3. An article according to claim 1 or 2, characterized in that said filler (2) is present in a weight percentage between 50 and 65% and said polymer (4) is present in a weight percentage between 35 and 50%.

7. 2. The article according to claim 1, characterized in that the metal and / or ceramic material comprises coordination and ionic bonds with the polymer (4) and / or the binder (3) on surface oxides, hydroxides and / or electron holes contained within hydrogen.

8. 3. The article of claim 2, characterized in that the metal and / or ceramic material comprises coordination and ionic bonds with the polymer (4) on surface oxides, hydroxides, and / or electron holes contained within hydrogen.

9. 2. The article according to claim 1, characterized in that the polymer (4) and / or the binder (3) have one or more groups selected from amine functional groups, OH, COC, C=O and COOH.

10. 3. The article according to claim 2, characterized in that said polymer (4) has one or more groups selected from amine functional groups, OH, COC, C=O and COOH.

11. 2. The article according to claim 1, characterized in that the polymer (4) is bonded to the filler (2) and / or, if the material comprises at least one binder (3), the binder (3) is bonded to the polymer (4) and to the filler (2) respectively by one or more ionic bonds, the polymer (4) having amine functional groups bonded to the anions of the filler (2) and / or the binder (3).

12. 3. An article according to claim 2, characterized in that said polymer (4) has amine functional groups which are bonded to the anions of said filler (2).

13. An article according to claim 11 or 12, characterized in that the filler (2) has O- anions.

14. 12. An article according to claim 11, characterized in that the binder (3) has an R-COO- anion.

15. 2. The article according to claim 1, characterized in that the polymer (4) is bonded to the filler (2) and / or, if the material comprises at least one binder (3), the binder (3) is bonded to the polymer (4) and to the filler (2) respectively by one or more coordinate bonds, the polymer (4) and / or the binder (3) having amine or carboxylic acid functional groups which create the coordinate bonds with electron holes on the surface of the filler (2).

16. 3. An article according to claim 2, characterized in that said polymer (4) has amine or carboxylic acid functional groups which form said coordinate bonds with electron holes on the surface of said filler (2). 。

17. 3. An article according to claim 1 or 2, characterized in that the reinforcing agent is present in a weight percentage between 0 and 6%.

18. 13. A method for manufacturing the article of claim 1, comprising: a) providing a substrate for the filler (2), the polymer (4) and optionally the binder (3), the reinforcing agent and the pigment, The filler (2) has a density of 3 g / cm 3 and the filler (2) is present in a weight percentage of 50% or more and 85% or less, said polymer (4) is present in a weight percentage equal to or greater than 15% and equal to or less than 50%; said binder (3) is present in a weight percentage equal to or greater than 0% and less than 10%; said reinforcing agent is present in a weight percentage between 0 and 10%; said pigments are present in a weight percentage between 0 and 5%; - the spreading agent and / or the plasticizer are present in a weight percentage between 0 and 5%; b) shaping said substrate by injection molding or 3D printing techniques to produce said article; The substrate for the filler (2) is 0.01 m 2 / g or more, and after the shaping step, the polymer (4) is bonded to the filler (2) and / or, if the material comprises at least one binder (3), the binder (3) is bonded to the polymer (4) and to the filler (2) respectively by one or more hydrogen bonds, said polymer (4) and / or said binder (3) are characterized in that they contain a hydrogen bond donor, said hydrogen bond donor being an amine functional group adjacent to a hydrogen bond acceptor, which is a C=O group, so as to generate a (C=O)NH unit; The (C=O)NH units represent at least 1 mol % of the polymer (4) and / or the binder (3).

19. 3. A method for manufacturing the article of claim 2, comprising the steps of: a) providing a substrate for the filler (2), the polymer (4) and, optionally, the reinforcing agent and the pigment, The filler (2) has a density of 3 g / cm 3 and the filler (2) is present in a weight percentage of 50% or more and 85% or less, said polymer (4) is present in a weight percentage equal to or greater than 15% and equal to or less than 50%; said reinforcing agent is present in a weight percentage between 0 and 10%; said pigments are present in a weight percentage between 0 and 5%; - the spreading agent and / or the plasticizer are present in a weight percentage between 0 and 5%; b) shaping said substrate by injection molding or 3D printing techniques to produce said article; The substrate for the filler (2) is 0.01 m 2 / g or more, The polymer (4) is characterized in that it comprises a hydrogen bond donor, which is an amine functional group adjacent to a hydrogen bond acceptor, which is a C=O group, so as to generate a (C=O)NH unit; The (C=O)NH units represent at least 1 mol % of the polymer (4).

Citation Information

Patent Citations

  • Oscillating mass

    EP2482142A1

  • Preparation of highhspecific gravity thermoplastic resin composition

    JP1980078032A

  • Case for wristwatch

    JP1985245668A

  • Composite polymer composition

    JP1988225657A

  • stationery

    JP1988265962A